A review of thermal methods and technologies for diabetic foot assessment. (July 2015) - Sousa, Paula; Felizardo, Virginie; Oliveira, Daniel; Couto, Rafael; Garcia, Nuno M
<x xml:space="preserve">Abstract</x> Temperature analysis has been considered as a complementary method in medical evaluation and diagnosis. Several studies demonstrated that monitoring the temperature variations of the feet of diabetic patients can be helpful in the early identification of diabetic foot manifestations, and also in changing behaviors, which may contribute to reducing its incidence. In this review, several and most used techniques for assessing the temperature of the feet are presented, along with original published work on specific applications in diabetic foot complications. A review of solutions and equipment that operate according to the temperature assessment techniques is also presented. Finally, a comparison between the various technologies is presented, and the authors share their perspective on what will be the state of affairs in 5 years.